2022
DOI: 10.7554/elife.76257
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic cis-regulatory evolution drives transcriptional partitioning of HERVH endogenous retrovirus in the human embryo

Abstract: The human endogenous retrovirus type-H (HERVH) family is expressed in the preimplantation embryo. A subset of these elements are specifically transcribed in pluripotent stem cells where they appear to exert regulatory activities promoting self-renewal and pluripotency. How HERVH elements achieve such transcriptional specificity remains poorly understood. To uncover the sequence features underlying HERVH transcriptional activity, we performed a phyloregulatory analysis of the long terminal repeats (LTR7) of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 117 publications
7
46
0
Order By: Relevance
“…Discovery of a complex polyphyletic composition of LTR7 elements comprising of at least eight monophyletic subfamilies (Carter et al, 2022) prompted sequence conservation analyses of each individual monophyletic subfamilies of LTR7 loci in genomes of sixteen NHP. Results of these analyses suggest that diversification of LTR7 loci into genetically and regulatory distinct subfamilies may have occurred early during primate evolution and subsequent cycles of LTR7 expansion appear to faithfully maintain this diversity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Discovery of a complex polyphyletic composition of LTR7 elements comprising of at least eight monophyletic subfamilies (Carter et al, 2022) prompted sequence conservation analyses of each individual monophyletic subfamilies of LTR7 loci in genomes of sixteen NHP. Results of these analyses suggest that diversification of LTR7 loci into genetically and regulatory distinct subfamilies may have occurred early during primate evolution and subsequent cycles of LTR7 expansion appear to faithfully maintain this diversity.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 3354 LTR7 loci and 606 LTR5_Hs loci residing at fixed non-polymorphic locations in genomes of Modern Humans (hg38 human reference genome database) analyzed in this study were reported previously (Carter et al, 2022; Fuentes et al, 2018). Solely publicly available datasets and resources were used in this contribution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations